Composition and Dynamics of the Nucleolinus, a Link between the Nucleolus and Cell Division Apparatus in Surf Clam (Spisula) Oocytes - Alliegro, Mark C. (American Society for Biochemistry and Molecular Biology, 2012)
The nucleolinus is a little-known cellular structure, discovered over 150 years ago (Agassiz, L. (1857) Contributions to the Natural History of the United States of America, First Monograph, Part IIL, Little, Brown and Co., Boston) and thought by some investigators in the late 19th to mid-20th century to function in the formation of the centrosomes or spindle. A role for the nucleolinus in formation of the cell division apparatus has recently been confirmed in oocytes of the surf clam, Spisula solidissima (Alliegro, M. A., Henry, J. J., and Alliegro, M. C. (2010) Proc. Natl. Acad. Sci. U.S.A. 107, 13718–13723). However, we know so little about the composition and dynamics of this compartment, it is difficult to construct mechanistic hypotheses or even to be sure that prior reports were describing analogous structures in the cells of mammals, amphibians, plants, and other organisms where it was observed. Surf clam oocytes are an attractive model to approach this problem because the nucleolinus is easily visible by light microscopy, making it accessible by laser microsurgery as well as isolation by common cell fractionation techniques. In this report, we analyze the macromolecular composition of isolated Spisula nucleolini and examine the relationship of this structure to the nucleolus and cell division apparatus. Analysis of nucleolinar RNA and protein revealed a set of molecules that overlaps with but is nevertheless distinct from the nucleolus. The proteins identified were primarily ones involved in nucleic acid metabolism and cell cycle regulation. Monoclonal antibodies generated against isolated nucleolini revealed centrosomal forerunners in the oocyte cytoplasm. Finally, induction of damage to the nucleolinus by laser microsurgery altered the trafficking of α- and γ-tubulin after fertilization. These observations strongly support a role for the nucleolinus in cell division and represent our first clues regarding mechanism.